PENGARUH KECERDASAN EMOSIONAL, NORMA SUBJEKTIF, DAN KONTROL PERILAKU PADA MINAT BERKARIR MAHASISWA PENDIDIKAN PROFESI AKUNTANSI - Kumala Dewi, Ni Kadek Diah; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 20 No 2 (2017)DO - 10.24843/EJA.2017.v20.i02.p06, 2017)
This research aimed to determine the effect of emotional intelligence, subjective norm, and control the behavior of the student career interests PPAk be a public accountant. The theory used in this research is the Theory of Planning Behavior and Theory of Reasoned Action. The population in this study were students who are still active PPAk year 2015/2016 at the Faculty of Economics and Business, University of Udayana. The samples used were 31 respondents to the sampling technique is sampling methods saturated. Collecting data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that emotional intelligence, subjective norms and behavioral control of a positive effect on student career interests PPAK be a public accountant.
Keywords: emotional intelligence, subjective norms, behavioral control, student career interests